Malaria and Typhoid Fever Coinfection in the Hospital University of Bobo-Dioulasso, Burkina Faso - Sangaré, Ibrahim; Sourabié, Yacouba; Bazié, Wilfried Wenceslas; Sirima, Constant; Da, Fabrice; Sanou, Do Soufiane; Zoungrana, Jacques; Poda, Armel; Ouédraogo, Abdoul Salam; Bamba, Sanata (Journal of Parasite Research, 2019)
Malaria and typhoid fever are two endemic infectious diseases in developing tropical countries including Burkina Faso. There are two distinct infectious diseases with many similar clinical signs. In each sanitary area, it is important to describe the "typhomalaria" epidemiology to elaborate adequate diagnosis algorithm and efficient treatment protocol. A cross-sectional study was carried out from July to October 2014 in the lab department of University Hospital Souro SANOU, Bobo-Dioulasso. All microscopy positive malaria during the study period was included. Serodiagnosis of Widal and Felix was performed systematically in all Plasmodium spmalaria cases. Titers of antibodies anti-agglutinin O equal or higher than 1/400 and/or 1/800 for anti-agglutinin H antibodies were considered positive for Salmonella sp. A total of 283 malaria cases were included in this study, majority falciparum malaria. In this malaria cases, 91 patients were seropositive for Salmonella sp. "Typhomalaria" co-infection prevalence was 34.3% (CI 95% (28.8%; 40.1%)). The patient with the normal hemoglobin rate had the highest prevalence of co-infection (46.7% versus 30.9; p=0.02). Malaria and typhoid fever co-infection was high (approximately 1/3 of malaria cases) in University hospital of Bobo-Dioulasso. This study revealed the need to explore typhoid fever in malaria confirmed cases, especially in persistent fevers and non-anemic situation despite adapting antimalarial treatment.
Keywords: Malaria; Typhoid fever; University Hospital; Co-infection; Burkina Faso